METHODS OF TEACHING METAPHORS - Rajabov Feruz, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation: The article discusses the role of metaphors in English as a Second Language  (ESL)  acquisition,  emphasizing  their  importance  in  enhancing  learners’ reading,  vocabulary  retention,  and  critical  thinking  skills.  It  highlights  common challenges,  such  as  cultural  differences  in  metaphorical  imagery  and  teachers’ tendency to underestimate the value of metaphor instruction. The authors argue that metaphors should be integrated into vocabulary teaching, as they are part of everyday communication  and  essential  for  developing  communicative  competence.  Various techniques are suggested for different proficiency levels, including matching exercises, metaphor  identification  in  argumentative  texts,  creative  rephrasing,  and  using advertising materials to foster metaphor awareness. The study underlines that working with metaphors not only strengthens language skills but also promotes cross-cultural understanding, creativity, and critical evaluation.